Sharing Breath: Embodied Learning and Decolonization - Edited by Sheila Batacharya and Yuk-Lin Renita Wong (Athabasca University Press, 2018)
Treating bodies as more than discursive in social research can feel out of place in academia. As a result, embodiment studies remain on the outside of academic knowledge construction and critical scholarship. However, embodiment scholars suggest that investigations into the profound division created by privileging the mind-intellect over the body-spirit are integral to the project of decolonization. The field of embodiment theorizes bodies as knowledgeable in ways that include but are not solely cognitive. The contributors to this collection suggest developing embodied ways of teaching, learning, and knowing through embodied experiences such as yoga, mindfulness, illness, and trauma. Although the contributors challenge Western educational frameworks from within and beyond academic settings, they also acknowledge and draw attention to the incommensurability between decolonization and aspects of social justice projects in education. By addressing this tension ethically and deliberately, the contributors engage thoughtfully with decolonization and make a substantial, and sometimes unsettling, contribution to critical studies in education.